Venture Capital and the Future of Corporate Finance - George W. Dent Jr. (Washington University Law Quarterly, 1992)
After discussing general venture capital principles, this Article analyzes how venture capitalists protect themselves against the managerial opportunism that plagues other passive investors. The Article then shows that venture capital, though not the long-sought panacea for minority shareholders, offers valuable lessons for both close and public corporations. Finally, the Article demonstrates that venture capital confirms Jensen's insight into the strength of private equity financing; thus, venture capital has the potential to transform corporate finance. To fully realize this potential, however, the law must change to better accommodate minority investors.
Keywords: Mutual funds; Corporations – Finance; Minority stockholders; Venture capital